2021
DOI: 10.1017/dmp.2021.175
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Each Other Safe: Who Checks on Their Neighbors During Weather Extremes in Summer and Winter?

Abstract: Objective: Weather extremes are increasing with climate change and associated with higher morbidity and mortality. Promotion of social connections is an emerging area of research and practice for risk reduction during weather extremes. This study examines the practice of checking on neighbors during extreme summer heat and extreme winter weather. Objectives are to (1) describe the extent of neighbor checking during these extremes, and (2) examine factors associated with neighbor checking. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…Consistent with findings from a primarily low- and moderate- income study sample in a southeastern U.S. city [ 66 ], only one-quarter of our study participants reported being contacted by someone in their family or social networks during a heat wave to inquire about their health and well-being. This may be due to average age of these households, as older adults have been reported elsewhere to be the primary beneficiaries of such checkups [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with findings from a primarily low- and moderate- income study sample in a southeastern U.S. city [ 66 ], only one-quarter of our study participants reported being contacted by someone in their family or social networks during a heat wave to inquire about their health and well-being. This may be due to average age of these households, as older adults have been reported elsewhere to be the primary beneficiaries of such checkups [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with findings from a primarily low- and moderate- income study sample in a southeastern U.S. city [ 66 ], only one-quarter of our study participants reported being contacted by someone in their family or social networks during a heat wave to inquire about their health and well-being. This may be due to average age of these households, as older adults have been reported elsewhere to be the primary beneficiaries of such checkups [ 66 , 67 ]. Additionally, in contrast with previous research documenting limited advanced warning of heat-related events among low-income households [ 9 , 43 ], a large majority of the low-income residents in this study had received advanced warnings from television news and social media.…”
Section: Discussionsupporting
confidence: 87%